Critical Issues in Vocational Education An Industrialist's View. Occasional Paper No. 95 - Elliman, Peter J.; Ohio State Univ., Columbus. National Center for Research in Vocational Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
On an overall basis, the United States is still the cheapest free world country in which to produce goods. If the United States is to retain this distinction, however, steps must be taken to reverse the trend toward yearly declines in the rate of gain in U.S. productivity. One way in which vocational education can help increase the productivity of the American labor force is to place less emphasis on the job- and industry-specific skills that can be taught most effectively by industry itself and to concentrate instead on preparing students for a world of work in which they must never cease learning and growing. In general, vocational education has neither the facilities nor personnel to provide effective training in high technology areas. What vocational education can do, however, is to train workers in the basic, transferable skills that they will need to succeed in the job-specific training that is best provided by the private sector itself. Vocational educators also need to develop courses that will teach students how to handle, manage, and just get along with others. To do this most effectively, teachers and administrators alike must make increased efforts to ascertain first hand exactly what skills business and industry require of their prospective employees. (A series of questions and answers is appended.) (MN)
Availability: National Center Publications, National Center for Research in Vocational Education, 1960 Kenny Road, Columbus, OH 43210-1090 (OC95--$2.50).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Business; Business Responsibility; Change Strategies; Comparative Analysis; Coordination; Economic Development; Educational Cooperation; Educational Needs; Employee Attitudes; Industry; Interpersonal Competence; Job Training; Labor Force; Labor Needs; Labor Relations; Needs Assessment; Postsecondary Education; Productivity; Public Policy; School Business Relationship; School Role; Secondary Education; Standards; Vocational Education; Work Attitudes; Private Sector; South Carolina; Opinion Papers